Corporate Environmental Responsibility for a Sustainable Future - Mulia, Pankojini; Behura, Ajit Kumar; Kar, Sarita (Problemy Ekorozwoju, 2017)
It is an imperative to find a proper way to maintain a balance between the economic development and natural environment’s carrying capacity, which is needed for the wellbeing and sustenance of human as well as non-human world. Balancing the economic growth and environmental quality has always been a challenge for business. In recent years, business has brought immeasurable wealth and prosperity. However, it has also caused unintended environmental degradation. Economic development is necessary to face the need of growing population but it should not add to a deteriorating environment. There is a need for broader ethical responses for environmental sustainability. The search for a sustainable future requires an integration of economic development with ethical objectives and scientific knowledge. Sustainability is a concept of continuance, relationships, and orientations. The paper deals with three interrelated ethical concepts, (1) corporate moral status, (2) corporate moral status to include human beings, (3) corporate moral status to include natural environment as a path of environmental sustainability.